Leadership, Discipline, and Organizational Culture on Job Satisfaction and Teacher Performance at State Junior High Schools in Bandar Petalangan District, Pelalawan Regency - Imarni; Teddy Chandra; Yanti Mayasari Ginting (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to determine and analyze the influence of leadership, discipline, and organizational culture on job satisfaction and teacher performance at SMP Negeri Bandar Petalangan. The number of samples in this study was the entire research population of 48 junior high school teachers in Bandar Petalangan District. Data analysis using Structural Equation Modeling (SEM) using SmartPLS 3.0 application. The results of this study indicate that leadership has a positive and insignificant effect on job satisfaction, discipline has a positive and significant effect on job satisfaction, organizational culture has a positive and insignificant effect on job satisfaction, leadership has a positive and insignificant effect on teacher performance, discipline has a positive and not significant effect on job satisfaction. significant effect on teacher performance, organizational culture has a positive and insignificant effect on teacher performance and job satisfaction has a positive and insignificant effect on teacher performance.